Common Purse, Uncommon Future the Long, Strange Trip of Communes and Other Intentional Communities - Manzella, Joseph C. (Praeger, 2010)
Common Purse, Uncommon Future: The Long, Strange Trip of Communes and Other Intentional Communities explores the many new types of communal living being tried in America and Europe today. A growing number of people disenchanted with the pressures and demands of mainstream lifestyles are drawn by the nostalgic appeal of traditional, mostly agrarian and artisanal, lifestyles as practiced in residential communities where liminal rituals of membership serve to validate pacts to live and work together in cooperative social and economic relations.
Keywords: Collective settlements; History; History; Communitarianism; United States; dept.ant; faculty_collection

Quantifying variation in landscape-scale behaviors: The oldowan from Koobi Fora - Braun, D.R.; Rogers, M.J.; Harris, J.W.; Walker, S.J. (New Perspectives on Old Stones: Analyt. Approaches to Paleolithic Technol., 2010)
Studies of stone artifact morphology are beginning to rapidly increase in complexity. While these techniques provide new insights into artifact variation, it is also necessary to insure that these methods provide data that is behaviorally relevant. Here, we provide a new technique that includes three dimensional attributes to calculate platform areas to enhance the prediction of flake area from platform attributes. This data allows the calculation of more precise measures of reduction in large unifacial flake cores in Developed Oldowan assemblages (i.e., Karari Scrapers). Here, we look at measures of curation within these tool types across a landscape scale study. We apply demographic analyses of the degree to which an assemblage can be considered to be curated (i.e., the potential use life of a tool minus the actual use life of a tool). Results suggest that even though there is significant variation within a given paleogeographic setting, a higher frequency of pieces are used to their full potential in areas where raw material is predicted to have been scarce. These data suggest that hominins fulfill some aspects of a neutral model of artifact transport, yet likely make directed movements to transport tools to specific places on the ancient landscape. © 2010 Springer-Verlag New York.
Keywords: dept.ant; ⛔ No DOI found

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

Trophy-taking and dismemberment as warfare strategies in prehistoric central California. - Andrushko, Valerie A; Schwitalla, Al W; Walker, Phillip L (American Journal of Physical Anthropology, 2010)
We document evidence for trophy-taking and dismemberment with a new bioarchaeological database featuring 13,453 individuals from prehistoric central California sites. Our study reveals 76 individuals with perimortem removal of body parts consistent with trophy-taking or dismemberment; nine of these individuals display multiple types of trophy-taking and dismemberment for a total of 87 cases. Cases span almost 5,000 years, from the Early Period (3000-500 BC) to the Late Period (AD 900-1700). Collectively, these individuals share traits that distinguish them from the rest of the population: a high frequency of young adult males, an increased frequency of associated trauma, and a tendency towards multiple burials and haphazard burial positions. Eight examples of human bone artifacts were also found that appear related to trophy-taking. These characteristics suggest that trophy-taking and dismemberment were an important part of the warfare practices of central Californian tribes. Temporally, the two practices soared in the Early/Middle Transition Period (500-200 BC), which may have reflected a more complex sociopolitical system that encouraged the use of trophies for status acquisition, as well as the migration of outside groups that resulted in intensified conflict. Overall, trophy-taking and dismemberment appear to have been the product of the social geography of prehistoric central California, where culturally differentiated tribes lived in close proximity to their enemies.
Keywords: *Corpse Dismemberment/hi [History]; *Fossils; *Social Behavior; Bioarchaeology; California; Corpse Dismemberment; Cutmarks; Fossils; History, Ancient; Humans; Male; Native American; Social Behavior; Trauma; United States; Violence; War; Warfare; article; artifact; autopsy; dept.ant; ethnic group; ethnicity; female; geography; human; injury; major clinical study; male; migration; peer-reviewed; physical anthropology; posthumous care